Is the addition of a neurokinin-1 receptor antagonist beneficial in moderately emetogenic chemotherapy?: a systematic review and meta-analysis - Jordan, Karin; Müller-Tidow, Carsten (Supportive care in cancer, 2018)
Purpose: This systematic review evaluates the efficacy of neurokinin-1 receptor antagonists (NK1RAs) for the prevention of chemotherapy-induced nausea and vomiting (CINV) in moderately emetogenic chemotherapy (MEC) excluding anthracycline-cyclophosphamide-based regimens. Methods: A systematic review of MEDLINE (via PubMed and OVID) and Central databases, plus major oncology conferences, identified randomized trials evaluating NK1RAs in combination with a 5-HT3 RA plus a glucocorticoid for management of CINV. Efficacy endpoints were complete response (CR), no emesis and no nausea rates. Data were analyzed using a random effects model. Results: Sixteen trials (3848 patients) were identified. Results were separately analyzed for (a) pure MEC regimens (excluding regimens containing carboplatin or oxaliplatin), (b) carboplatin-based regimens, and (c) oxaliplatin-based regimens. (a) Two trials (abstracts) enrolled 715 patients. The odds ratio for overall CR with the addition of an NK1-RA was 1.46 (95% 1.06-2.02; p = 0.02) with an absolute risk difference (RD) of 8%. (b) Nine trials (1790 patients) were identified. The OR for achieving an overall CR was 1.96 (95% CI 1.57-2.45; p < 0.00001) in favor of the NK1RA containing regimen with an RD of 15%. (c) Three trials (1190 patients) were identified. The OR for achieving an overall CR was 1.34 (95% CI 0.88-2.04; p = 0.17) not reaching statistical significance with a RD of 4%. Conclusion: Clear clinically significant benefit was seen with the addition of NK1RAs in carboplatin-based chemotherapy. A global benefit of an NK1RA containing regimen for the whole MEC category cannot be attested yet and warrants more randomized trials exclusively testing pure MEC regimens without carboplatin.